My Brother's Keeper: Mass Death in the Carceral State - Chavez, Ernest K. (Social justice, 2016)
As the number of prisoners in the United States who die from terminal illness, old age, and deteriorating health conditions reaches unparalleled proportions, scholars who study punishment ought to extend their focus to the ways in which mass incarceration is producing what is referred to in this work as mass death. By centering on sites of physiological death that exist inside of US prisons such as prison hospices, prison deathbeds, funerals, and cemeteries, this article attempts to illustrate the ways in which the carceral state constructs and justifies mass death.